2019
DOI: 10.1007/s10815-019-01423-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment of human sperm DNA damage II: the effect of sperm concentration adjustment during processing

Abstract: Purpose To evaluate the effect of sperm concentration adjustment in human ejaculates on the sperm DNA quality and longevity. Methods Semen samples were obtained from 30 donors with a normal spermiogram. Following centrifugation, the sperm pellet was resuspended in PBS, and the sperm concentration adjusted to 200, 100, 50, 25, 12, and 6 × 10 6 /mL. Each set of samples was incubated at 37 °C for 24 h, and the sperm DNA damage was assessed using the chromatin-dispersion test following 0 h, 2 h, 6 h, and 24 h of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…With regard to the effect of sperm concentration on DNA fragmentation, we observed that sDFI was higher when sperm concentration increased. It was observed that DNA longevity depends largely on sperm concentration during incubation [ 56 ]. After incubation at 37 °C, the DNA fragmentation rate was greater in samples with high sperm concentration, but it had a significant individual effect [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the effect of sperm concentration on DNA fragmentation, we observed that sDFI was higher when sperm concentration increased. It was observed that DNA longevity depends largely on sperm concentration during incubation [ 56 ]. After incubation at 37 °C, the DNA fragmentation rate was greater in samples with high sperm concentration, but it had a significant individual effect [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that DNA longevity depends largely on sperm concentration during incubation [ 56 ]. After incubation at 37 °C, the DNA fragmentation rate was greater in samples with high sperm concentration, but it had a significant individual effect [ 56 , 57 ]. One explanation could be that an increase in oxidative stress (e.g., H 2 O 2 ) occurs when spermatozoa are stored at high concentrations [ 4 , 15 ], and it is known that an increase in oxidative stress induces nuclear and mitochondrial DNA damage [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…All slides were stained using SYBR Green (2 μg/mL) (Sigma-Aldrich, St. Louis, MO, USA) in VECTASHIELD (Vector Laboratories, Burlingame, CA, USA) and a minimum of 300 spermatozoa per sample was scored using an Epifluorescence Leica DMI6000 microscope using a dry ×40 fluorite magnification objective (Leica Microsystems, Wetzlar, Germany). The incidence of DNA fragmented spermatozoa was expressed in percentages (%) [42].…”
Section: Assessment Of Sperm Dna Integritymentioning
confidence: 99%
“…Analysis of the halo diameter was used as a quantitative parameter for DNA breaks (chromatin damage intensity), whereas the percentage of sperm with fragmented DNA was determined by classifying 400 sperm haloes using the criteria defined for sperm DNA fragmentation (40).…”
Section: Alkaline and Neutral Chromatin Dispersion Assaymentioning
confidence: 99%